Spatial-temporal analysis of ecosystem services value and research on ecological compensation in Taihu Lake Basin of Jiangsu Province in China from 2005 to 2018 - Gao, Xin; Shen, Juqin; He, Weijun; Zhao, Xu; Li, Zhichao; Hu, Weifang; Wang, Jingzhe; Ren, Yingjie; Zhang, Xin (Journal of cleaner production, 2021)
The existing research on watershed ecological compensation pays less attention to the special basin (without significant relationship between upstream and downstream or the compensation subject and object are distributed on the left and right banks of the basin), which makes the previous research methods difficult to be effectively used. Therefore, it is necessary to explore a new method to solve the problem of ecological compensation in special basin. Taking Taihu Lake Basin (Jiangsu section) as an example, this paper first calculates the ecosystem service value (ESV) of the region from 2005 to 2018, and makes a spatial-temporal analysis; through the construction of land use intensity index system and coupling coordination degree model, the relationship between ESV and land use intensity is explored, and the reasons for its change are explored; finally, this paper constructs a compensation standard accounting model based on GDP, basin area and population, and applies it to the accounting of compensation standard and the identification of compensation subject and object. The results show that: from 2005 to 2018, the land use of this area changed greatly, mainly reflected in farmland and urban land; ESV decreased by 21.41%, which was mainly affected by the change of land use, the downturn of grain market, and farmers' going out to work; the coupling coordination degree of land use intensity and ESV in this area entered the stage of coordinated development from 2010, but the situation of each city was quite different; population, area and GDP have a great influence on compensation subject and object, and compensation standard. This study can not only provide a complete methodology for governments to implement ecological compensation in special basins, and improve the existing ecological compensation theory.